Graphene quantum dots induced defect-rich NiFe Prussian blue analogue as an efficient electrocatalyst for oxygen evolution reaction - Lin, Yin-Chen; Aulia, Sofiannisa; Yeh, Min-Hsin; Hsiao, Li-Yin; Tarigan, Angelina Melanita; Ho, Kuo-Chuan (Journal of colloid and interface science, 2023)
[Display omitted] High energy resource demand has led to the rapid development of hydrogen as a clean fuel through electrolytic water splitting. The exploration of high-performance and cost-effective electrocatalysts for water splitting is a challenging task to obtain renewable and clean energy. However, the sluggish kinetics of oxygen evolution reaction (OER) greatly hindered its application. Herein, a novel oxygen plasma-treated graphene quantum dots embedded Ni-Fe Prussian blue analogue (O-GQD-NiFe PBA) is proposed as a highly active electrocatalysts for OER. Furthermore, the defect induced by GQD can provide an abundant lattice mismatch in the matrix of NiFe PBA, which further facilitates faster electron transport and kinetic performance. After optimization, the as-assembled O-GQD-NiFe PBA exhibits excellent electrocatalytic performance towards OER with a low overpotential of 259 mV for reaching a current density of 10 mA cm−2 and impressive long-term stability for 100 h in an alkaline solution. This work broadens the scope of metal–organic frameworks (MOF) and high-functioning carbon composite as an active material for energy conversion systems.